Performance Predictions of Dry and Wet Vapors Ejectors Over Entire Operational Range - Fenglei Li; Zhao Chang; Qi Tian; Changzhi Wu; Xiangyu Wang (Energies, 2017)
If a traditional ideal-gas ejector model is used to evaluate the performance of a wet vapor ejector, large deviations from the experimental results will be unavoidable. Moreover, the model usually fails to assess the ejector performance at subcritical mode. In this paper, we proposed a novel model to evaluate the performance of both dry and wet vapors ejectors over the entire operational range at critical or subcritical modes. The model was obtained by integrating the linear characteristic equations of ejector with critical and breakdown points models, which were developed based on the assumptions of constant-pressure mixing and constant-pressure disturbing. In the models, the equations of the two-phase speed of sound and the property of real gas were introduced and ejector component efficiencies were optimized to improve the accuracy of evaluation. It was validated that the proposed model for the entire operational range can achieve a better performance than those existing for R134a, R141b and R245fa. The critical and breakdown points models were further used to investigate the effect of operational parameters on the performance of an ejector refrigeration system (ERS). The theoretical results indicated that decreasing the saturated generating temperature when the actual condensing temperature decreases, and/or increasing the saturated evaporating temperature can improve the performance of ERS significantly. Moreover, superheating the primary flow before it enters the ejector can further improve the performance of an ERS using R134a as a working fluid.